BIODIVERSITY OF WEEDS IN POTATO (SOLANUM TUBEROSUM) IN PANGALENGAN AND CIKAJANG SUB-DISTRICTS OF INDONESIA - Umiyati, Uum (Potato Journal, 2023)
ABSTRACT: Potato is one of the horticulture crops with the highest economic worth and the steadiest market interests.Weeds can affect agricultural output through competition for nutrients and water, sunlight for photosynthesis, and growingspace. This study attempts to comprehend the proliferation of weeds in potato cultivation in West Java's Potato Centersof Pangalengan and Cikajang Subdistricts. The study was done between December 2020 and February 2021 using surveyand vegetation analysis techniques. The vegetative analysis demonstrates that the diversity of weeds in potato croppingin the Pangalengan and Cikarang Subdistricts led to precise results. Four kinds of grassy weeds, two sedges, and eightbroadleaf weeds were discovered in potato cropping throughout the Pangalengan Subdistrict. Two species of grassy weeds,two species of sedges, and eleven species of broadleaf weeds were discovered in the potato cropping across the CikarangSubdistrict, which contained a total of fifteen species. The weeds with the greatest SDR (Summed Dominance Ratio) valuesin these two regions were Cyperus rotundus and Eleusine indica. The species diversity index value (H'), which fell intothe medium category, and the community coefficient index value (C), which has significant degrees of difference, alsorevealed differences in diversity.